The DNA bend angle and binding affinity of an HMG box increased by the presence of short terminal arms. - Lnenicek-Allen, M (1996)
The HMG box of human LEF-1 (hLEF-1, formerly TCF1alpha) has been expressed in four forms: a parent box of 81 amino acids and constructs having either a 10 amino acid C-terminal extension, a 9 amino acid N-terminal extension, or both. These four species have been compared for DNA binding and bending ability using a 28 bp recognition sequence from the TCR alpha-chain enhancer. In the bending assay, whereas the parent box and that with the N-terminal extension bent the DNA by 57/58 degrees, the box extended at the C-terminus bent the DNA by 77/78 degrees, irrespective of the presence or absence of the N-terminal extension. A 6- fold increase in DNA affinity also resulted from addition of both terminal extensions. These observations redefine the functional boundaries of the HMG box. The structure of a mouse LEF-1/DNA complex recently published [Love et al. (1995) Nature 376, 791-795] implies that the higher DNA affinity and in particular the increased bend angle observed are consequences, at least in part, of the C-terminal extension spanning the major groove on the inside of the DNA bend.